Framework of Designing Multiple Microcontroller Based Applications - Selvakumar, Raja Saravana Kumar; Kamarul Hawari, Ghazali; Nik Mohd Kamil, Nik Yusof (2011)
This paper presents a framework for developing applications based on a three type of microcontroller (μC), Freescale HC11, MCS51 and Microchip PIC18. This project consists of the hardware and software implementation that supports the development and transfer process of the program code from a personal computer to the microcontroller, which led to the evaluation of educational based training kit systems. The first part of the paper focuses on hardware design, which is based on a modular approach, i.e. recomposed for the design of each application, in order to ensure maximum adaptability. The Multiple Microcontroller Evaluation Tool (microEVAT) thus consists of a programmer tool, a main board including adapters for a variety of chip packages, and plug-in modules. These are presented in the second part of the paper describing the software part of the framework, which besides programming tools also discusses the code development tools. The stress is given to the use of assembly code and high-level tools, where the algorithms are described in the form of different graphical notations, i.e. block diagrams. Throughout the paper, a special attention is given to the use of framework in the electronics engineering education process. Keywords: - PIC microcontrollers, HC11 microcontrollers, MCS51 microcontrollers Development system, Electronics engineering education